Data Transmission Using Multiple Medium Concurrently - Rose J, Dafni; K, Vijayakumar (International Journal of Engineering and Technology, 2018)
This article is an alternate way of data transferring using a new data transferring protocol. In conventional data transfer only one medium (either wired or wireless) is used, so other medium is idle. Thus by using both medium, the data transferring will be efficient, because the data is transferred in a parallel manner. In this method of data transfer the speed is increased by twice of the conventional method. This would be very helpful when a large file is to be transferred. In this project the wireless connection is established by socket programing and the wired connection is established by USB wire. The data is transferred by using apache java library that provides generic access to USB devices. In this technique the data is split into multiple chunks of particular size. The USB function and Wi-Fi function are threaded parallel .Thus the chunks are transferred in both medium simultaneously. The chunks are received through Wi-Fi and appended into a single file. Thus the data is transferred efficiently and accurately.Â Â Â